2, 5-diketopiperazines in food and beverages: Taste and bioactivity. Issue 4 (4th March 2017) - Borthwick, Alan D.; Da Costa, Neil C.
ABSTRACT: 2, 5-Diketopiperazines (2, 5-DKPs) have been found to occur in a wide range of food and beverages, and display an array of chemesthetic effects (bitter, astringent, metallic, and umami) that can contribute to the taste of a variety of foods. These smallest cyclic peptides also occur as natural products and have been found to display a variety of bioactivities from antibacterial, antifungal, to anthroprotective effects and have the potential to be used in the development of new functional foods. An overview of the synthesis of these small chiral molecules and their molecular properties is presented. The occurrence, taste, and bioactivity of all simple naturally occurring 2, 5-DKPs to date have been reviewed and those found in food from yeasts, fungi, and bacteria that have been used in food preparation or contamination, as well as metabolites of sweeteners and antibiotics added to food are also reviewed.